2013
DOI: 10.3390/su5125249
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Sustainability: Exploring the Views of Tenants in Supported Social Housing

Abstract: Government policy aimed at curbing carbon emissions often focusses on encouraging individual action, however the effectiveness of this approach has been limited. Investigations of why this might be have included segmentation, to identify different groups who undertake more or less action, and analysis of various -barriers‖ to action. Those on lower incomes who are not home owners have previously been found to be less engaged in seeking out energy efficiency information. Working with low-income tenants living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Participants showed that they had existing knowledge of a wide variety of relevant topics (in particular steps commonly promoted in campaigns, like switching appliances off standby), and any presumption that this demographic group would have little to say on, or little interest in, global issues such as climate change would be quite wrong. It was also found that they understood the importance of wellcommunicated information in promoting ERBs as well as the benefits that may be gained by teaching people early in life [20]. The latter can be seen through the comment that 'they learn this at schools nowadays, which I think is a good thing'.…”
Section: Comprehension and Dialogue: Phasementioning
confidence: 96%
See 1 more Smart Citation
“…Participants showed that they had existing knowledge of a wide variety of relevant topics (in particular steps commonly promoted in campaigns, like switching appliances off standby), and any presumption that this demographic group would have little to say on, or little interest in, global issues such as climate change would be quite wrong. It was also found that they understood the importance of wellcommunicated information in promoting ERBs as well as the benefits that may be gained by teaching people early in life [20]. The latter can be seen through the comment that 'they learn this at schools nowadays, which I think is a good thing'.…”
Section: Comprehension and Dialogue: Phasementioning
confidence: 96%
“…Initiating new ERBs is not straightforward . Over two‐thirds of the UK population report that they wish to change their behaviour to be more environmentally friendly , yet significant lifestyle changes are not undertaken by many.…”
Section: Underpinnnings Of the Three‐phase Programmementioning
confidence: 99%
“…In research based on data from the European Social Survey into civic attitudes and the dimensions of citizenship in Europe, Jaime Castillo [16] concluded that European citizens with a higher educational level also had a higher level of civic commitment, thus confirming that the educational system has an important role in the transmission of civic attitudes. In this line of research, various other recent studies highlight the role of income and education in forming attitudes in favour of the environment and against climate change [17,18].…”
Section: Research Into Public Opinion On Aid Is Dominated By Comparatmentioning
confidence: 94%
“…It was during this analysis that the themes of home, sense of place and the concerns around moving to an LCD were identified as noteworthy. This paper is based on the further thematic analysis of the data with these themes in mind, following the method set out in [56] as well as the post-occupancy evaluation of how residents are experiencing life in the LCD. Quantitative methods are not the focus in this paper, however some results from the Likert scale questionnaire are discussed due to their relevance.…”
Section: Methodsmentioning
confidence: 99%